Identification of Calendula and Eucalyptus Alcoholic Tinctures Volatile Compounds in the Compounding Ointment by Gas Chromatographyâ€“mass Spectrometry - Savchenko, Lesia (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Alcoholic tinctures of Calendula officinalis and Eucalyptus globulus are often found in the extemporal dosage forms composition, including ointments. Their pharmacological effect is caused by the presence of biologically active substances, which determine the direction of dosage form action. Therefore, during the stability studies, it is necessary to evaluate their concentration in the dosage form. Aim: Development of the gas chromatographyâ€“mass spectrometry (GC/MS) method for the determination of the ointment with C. officinalis and E. globulus tinctures stability. Materials and Methods: In this research, the GC/MS method was used for determining the volatile compounds of both tinctures, with their subsequent determination in the compounding ointment containing them. Results and Discussions: Î±-cadinol, Î´-cadinene, t-muurolol, Î³-cadinene, viridiflorene, and Î±-muurolene were identified as the C. officinalis tincture main components. 1,8-cineole, Î±-pinene, aromadendrene, Ï-cymene, Î²-eudesmol, (-)-globulol, Î±-eudesmol, and Î²-pinene were isolated in the E. globulus tincture. Analysis of the ointment dissolved in chloroform had shown the presence of a small amount of the both tinctures main components. The same technique has been used to analyze the stability of ointment. The results of ointment research after storage at a temperature of 5 Â± 3Â°C for 18 days have been indicated decreasing of the main substances of plant tinctures concentration. Conclusions: Thus, developed GC/MS method allows to determine the concentration of active components of both tinctures and can be used to study the ointment chemical stability.